The Effect of Work Safety and Health (K3) on Production Departement Employee Performance at The Sugar Factory of PT. Nusantara Plantation XIV (Persero) in Takalar District - Adelia Ramadani; Muh. Rizal S; Aris Baharuddin (Fakultas Ilmu Sosial dan Hukum, 2024)
This study aims to determine how the influence of Work Safety and Health on the Performance of Production Section Employees either Simultaneously or Partially where the Takalar Sugar Factory PT. Nusantara Plantation XIV (Persero) became the object of his research. This research uses quantitative research. Data collection techniques used are primary data collection (observation, interviews and questionnaires) and secondary data collection (library review and documentation). The sample used is the sample formulated by Slovin as many as 70 respondents. The data obtained from the research results were processed using data analysis and using the help of the SPSS version 25 software program which consisted of validity tests, reliability tests on research instruments as well as descriptive statistical analysis techniques and inferential statistical analysis of the data that had been obtained. The results showed that the indicators used for each variable indicated that the occupational safety and health variables had a significant effect on the Performance of Production Section Employees at the Takalar Sugar Factory PT. Nusantara Plantation XIV (Persero). This is evidenced by the Correlation Test and the t-test and F-test and the Coefficient of Determination Test on the data that has been obtained.